2011
DOI: 10.1017/jfm.2011.210
|View full text |Cite
|
Sign up to set email alerts
|

Liquid spreading on superhydrophilic micropillar arrays

Abstract: When a drop is deposited on a superhydrophilic micropillar array, the upper part of the drop (referred to as the bulk) collapses while the bottom part penetrates into the gaps of the array, forming a fringe film. Here we quantify the early stage dynamics of this process using a combination of experiment and theory. We show that the circular front of the fringe film spreads like t1/2, t being time, when coupled to the bulk flow. However, the film is found to advance like t1/3 through faceted zippering in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 19 publications
12
74
0
Order By: Relevance
“…What is the physical mechanism of this transition? In figure 7(a,b) we can find that although R b expanded more slowly than R f , they scaled similarly, which is also validated by the experiments (Kim et al 2011). According to the MD simulations, we would assume αR b ∼ R f ∼ t n in the next section.…”
Section: Molecular Dynamics Simulationssupporting
confidence: 72%
See 2 more Smart Citations
“…What is the physical mechanism of this transition? In figure 7(a,b) we can find that although R b expanded more slowly than R f , they scaled similarly, which is also validated by the experiments (Kim et al 2011). According to the MD simulations, we would assume αR b ∼ R f ∼ t n in the next section.…”
Section: Molecular Dynamics Simulationssupporting
confidence: 72%
“…In the spreading process, αR b ∼ R f ∼ R is validated by Kim et al (2011) and our MD simulations, where α (α 1) is independent of time.…”
Section: Scaling Analysis Using Molecular Kinetic Theorysupporting
confidence: 62%
See 1 more Smart Citation
“…Courbin et al [25] reported the dynamics of shape evolution, while the mechanism in the process of evolution is still demanded. Kim and coworkers [26] quantified the dynamics of polygonal spreading and proposed the scaling laws for spreading rates of the bulk and the fringe separately, when the shape evolution of the bilayer structure has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, it has been shown that the symmetry of the pillar array typically controls the shape of the wetting front of the drop, which can be faceted as a square (or an octagon) when the drop is deposited on a square array of pillars, or as a hexagon on a hexagonal array [2,5,6]. Following these works, an intense more recent effort has been dedicated to analyzing how the geometrical characteristics of the texture influence the advancing front dynamics [7][8][9][10][11][12][13]. Interestingly, some peculiar "microscopic" mechanisms of contact line motion were evidenced in some of these works, such as the so-called zipping mechanism which consists in the wetting of an individual pillar of the next row by the liquid front, followed by lateral progression along this row [6,11].…”
mentioning
confidence: 99%